Euro Area Policies : 2021 Article IV Consultation with Member Countries on Common Euro Area Policies-Press Release; Staff Report; and Statement by the Executive Director for Member Countries. (IMF Staff Country Reports; Country Report ;, 2022)
Following a deep recession in 2020 and further contraction in 2021Q1, the euro area economy recovered rapidly in the second and third quarters thanks to high vaccination levels, increasing household and business adaptability to the virus, and continued forceful policy support. Looking ahead, while supply chain disruptions, elevated energy prices, and resurgences of Covid-19 cases-including those related to the Omicron variant-are likely to pose near-term headwinds to growth, the recovery is set to continue in 2022 as the impact of the pandemic on economic activity continues to weaken over time and supply-side constraints ease. Medium-term output losses relative to pre-crisis trends will vary significantly across countries and sectors as will the extent of labor market scarring. Price pressures are building up as production bottlenecks are set to persist for a while. However, inflation-despite increasing significantly in recent months due to transitory factors-is projected to moderate during 2022 and remain below the ECB's inflation target over the medium term. Uncertainty surrounding the outlook remains high and largely related to pandemic dynamics and legacies, including induced behavioral and preference changes.